Pengaruh Media TikTok terhadap Kemampuan Berpikir Historis dalam Pembelajaran Sejarah Berbasis Kurikulum Merdeka - Amara Raudhatul Jannah; Hieronymus Purwanta (Simpati, 2026)
This study aims to analyze the effect of TikTok media utilization on high school students’ historical thinking skills in history learning based on the Merdeka Curriculum. Historical thinking skills were measured through three components adapted from Seixas’ model, namely historical significance, continuity and change, and historical perspective. This research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The participants consisted of 63 tenth-grade students at SMA Batik 1 Surakarta selected through purposive sampling. Data were collected using historical thinking skill tests administered before and after the treatment and were analyzed to identify differences between the experimental and control groups. The results indicate that the use of TikTok media has a positive effect on improving students’ historical thinking skills. TikTok encourages student engagement, facilitates the understanding of historical concepts, and promotes critical analysis of past events. Therefore, TikTok can serve as an effective alternative medium for history learning within the Merdeka Curriculum when content is systematically designed and aligned with appropriate pedagogical principles.